Enterprise LMS with Adobe Captivate Prime Design and Develop World-Class Learning Experiences for Your Employees, Partners, and Customers. - Bruyndonckx, Damien (Packt Publishing, Limited, 2021)
Adobe Captivate Prime is an enterprise LMS platform that enables you to deliver world-class e-learning solutions. This book helps you unlock the full potential of this platform to help you publish content online, ensure that the right student accesses the content, track student progress, and evaluate the course's effectiveness and ROI.